Comparison of Financial Ratios Before and During the COVID-19 Pandemic in Islamic Banking in Indonesia - Moeiz, Ronny Ciptadi; Asrid Juniar (Open Access Indonesia Journal of Social Sciences, 2023)
The COVID-19 pandemic has not only changed the global economic landscape but also forced Islamic banks to reevaluate their strategies, operations and policies. In this context, a comparison of financial ratios before and during the pandemic is very important to identify significant changes that have occurred in Islamic banking performance. This pandemic has forced Islamic banks to review their business strategies. They must consider how to deal with declines in economic activity, changes in consumer behavior, and market fluctuations. This study aimed to compare financial ratios before and during the COVID-19 pandemic on Islamic Banking in Indonesia. This type of research is quantitative research with a descriptive approach. In this study, the sample size was all Islamic commercial banks at core capital adequacy Bank 1 in Indonesia, namely the ratio of operational costs - operational income (BOPO), allowance for impairment losses (CKPN), financing to deposit ratio (FDR), net operating margin (NOM), non-performing financing gross (NPF Gross), net non-performing financing (NPF Netto), return on asset (ROA) and return on equity (ROE) in the period before the COVID-19 pandemic and during the COVID-19 period. There is no difference in the financial performance of Islamic banks as measured by the BOPO, NOM, NPF, and ROE ratios before and during the COVID-19 pandemic. There are differences in the financial performance of Islamic banks as measured by the CKPN, FDR, and ROA ratios before and during the COVID-19 pandemic.